2016
DOI: 10.1016/j.jcorpfin.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Drivers behind the monitoring effectiveness of global institutional investors: Evidence from earnings management

Abstract: This paper studies the drivers behind the monitoring effectiveness of institutional investors in curbing earnings management in an international setting. We identify three distinct drivers and propose two competing hypotheses: the hometown advantage hypothesis predicts that because of proximity to monitoring information, domestic institutions have a comparative advantage over foreign institutions in deterring earnings management, whereas the global investor hypothesis predicts that foreign institutions have a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
115
2
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(176 citation statements)
references
References 57 publications
12
115
2
6
Order By: Relevance
“…Kim et al (2016) identified that these kinds of investors favors the reduction of earnings management. This is good news for Brazilian investors and Brazilian firms since a market with better result disclosure practices gains investor confidence and this should result in smaller capital costs.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Kim et al (2016) identified that these kinds of investors favors the reduction of earnings management. This is good news for Brazilian investors and Brazilian firms since a market with better result disclosure practices gains investor confidence and this should result in smaller capital costs.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Although empirical evidence confirms the existence of an institutional monitoring effect on earnings quality in Korea [1][2][3][4][5][6], we believe that blockholders in Korea influence managerial decision-making regarding firms' operations through passive monitoring rather than direct intervention. Edmans [25] and Admati and Pfleiderer [26] claim that even when large institutional investors are unable to intervene in firms' activities and can only sell their stakes or threaten to do so ("threat of exit"), these investors may influence managerial behavior.…”
Section: "Passive" Institutional Monitoring Channel and The Chaebol-dmentioning
confidence: 92%
“…Although the literature largely substantiates the institutional monitoring effect in Korea [1][2][3][4][5][6], the channel through which blockholders, that is, institutional investors with large shareholdings in firms, affect managerial behavior requires further consideration. Previous studies mainly assume that Korean blockholders actively participate in institutional monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Constatou-se também que, nas empresas da amostra, existe associação entre participação acionária de investidores institucionais e qualidade da informação contábil, assim como evidenciaram os achados de Koh (2007), Hadani et al (2011), Njah e Jarboui (2013), Lin et al (2014) e Kim et al (2016).…”
Section: Considerações Finaisunclassified